Effect of Oxidative Stress on Iraqi Rheumatoid Arthritis Patients - Hussain, Weaam F; Al-Hashemi, Wisam Kadhum H H (Al-Nahrain Journal of Science, 2018)
Oxidative stress is an imbalance between oxidants and antioxidants, play an important role in the development of Rheumatoid Arthritis. Rheumatoid Arthritis regard as a chronic, autoimmune disease. The aim of the study to assess levels of some oxidative stress biomarker in Rheumatoid Arthritis. This study involves 80 Rheumatoid arthritis patients and 30 healthy subjects as control groups. Analysis on serum samples was Malondialdehyde, Albumin, and total Bilirubin. The obtained data showed significantly increasing (P